ANALISIS RESPON MAHASISWA KOMUNIKASI DAN PENYIARAN ISLAM IAI AL-AZIS TERHADAP RETORIKA DAKWAH HABIB JAFAR DI TIKTOK - Sayidarrahmah, Dewi; Elang Bakhrudin; Wiena Safitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research discusses the rhetoric of da'wah practiced by Habib Jafar on TikTok. The study is motivated by the evolving times, which have made da'wah media more contemporary. One such contemporary medium, currently popular among young generations including students, is TikTok. Additionally, one of the prominent da'ees watched by this young audience is Habib Jafar. Based on this background, the research objectives are to understand the rhetoric of Habib Jafar on TikTok and to assess the response of Communication and Islamic Broadcasting students to Habib Jafar's da'wah rhetoric on TikTok. The research employs a qualitative-descriptive approach. Data sources are obtained from observations, interviews, and documentation. The analysis and description of the data use Aristotle's rhetorical theory, which includes ethos, logos, and pathos. The findings indicate that Habib Jafar's rhetoric can be explained by applying Aristotle's three rhetorical elements: ethos, pathos, and logos. In terms of ethos, he gains credibility as a trusted and respected source, as evidenced by the positive responses in the comments section of the observed videos. In the aspect of pathos, the emotional appeal of his da'wah is reflected through the intonation, tone, and language used. Meanwhile, in terms of logos, Habib Jafar employs logic by structuring his statements in an easily understandable manner and relating his da'wah messages to everyday life. The response from Communication and Islamic Broadcasting students from the 2019 cohort to Habib Jafar's da'wah rhetoric on TikTok is positive. This includes the ease of understanding his messages due to the clear and everyday language used, the moderate tone of intonation, relevance to current social contexts, and the credibility of the source. Keywords: Da'wah rhetoric, Habib Jafar, Response;